Kesabaran (Al-Ṣabr) dalam Al-Qur'an: Analisis Interpretasi Tematik, Semantik, dan Kontekstual - Nurwahid Syam; Muhmmad Yusuf; Mardan Mardan (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2026)
This article examines the concept of al-ṣabr in the Qur'an using a qualitative approach based on literature studies with the method of thematic interpretation (tafsīr mawḍū'ī). The research data is in the form of 90 verses of the Qur'an that contain the word